Núcleos ativos de galáxias: uma breve introdução - Sales, Dinalva Aires de (Cadernos de Astronomia, 2024)
Active Galactic Nuclei (AGN) are characterized by the presence of supermassive black holes (SMBHs) at their cores, which are involved in the acquisition of matter through an accretion disk. Within the AGN paradigm, a significant debate persists regarding the origin of this activity, encompassing triggering mechanisms and the impacts on dust and molecules in host galaxies. This work aims to describe the main observational characteristics of the classification and unification of active galactic nuclei, which can also be referred to in the literature simply as active galaxies.